Biochemical analysis of the W28F mutant of human class Pi glutathione S-transferase - Chien, Yu, Chen (My University, 1996)
Glutathione S-transferase (GST) class Pi has two tryptophan residues which are conserved within domain one. Trp38 plays a functional role in sequestering glutathione at the active site, whereas Trp28 plays a structural role. The effects of the sterically-conservative substitution of Trp28 to Phe were investigated. When the W28F mutant was compared with the wild-type enzyme, mutation of Ttp28 to Phe was not well tolerated and resulted in a dimeric protein with impaired catalytic function and conformational stability. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science at the University of the Witwatersrand. Johannesburg, October 1996.
Keywords: Glutathione transferase